Insecticidal Activity of Bacillus thuringiensis Strains on the Nettle Caterpillar, Euprosterna elaeasa (Lepidoptera: Limacodidae) - Angelica Plata-Rueda; Hughes Antonio Quintero; José Eduardo Serrão; Luis Carlos Martínez (Insects, 2020)
In the present work, we evaluated the insecticidal activity of Bacillus thuringiensis (Bt) strains on Euprosterna elaeasa as an alternative for the organophosphate insecticide use in oil palm plantations in the Americas. The toxic effects of four Bt-strains (HD-1 var. kurstaki, SA-12 var. kurstaki, ABTS-1857 var. aizawai, and GC-91 var. aizawai) were evaluated against E. elaeasa caterpillars for toxicity, survival, anti-feeding, and mortality in field-controlled conditions. The Bt-strains, ABTS-1857 var. aizawai (LC50 = 0.84 mg mL−1), GC-91 var. aizawai (LC50 = 1.13 mg mL−1), and HD-1 var. kurstaki (LC50 = 1.25 mg mL−1), were the most toxic to E. elaeasa. The caterpillar survival was 99% without exposure to Bt-strains, and decreased to 52–23% in insects treated with the LC50 and 10–1% in insects exposed to LC90 after 48 h. Furthermore, Bt-strains decreased significantly the consumption of oil palm leaves of E. elaeasa 3 h after exposure. Mortality of E. elaeasa caterpillars caused by Bt-strains had similar lethal effects in the laboratory and in field conditions. Our data suggest that Bt-strains have insecticidal activity against E. elaeasa and, therefore, have potential applications in oil palm pest management schemes.